Penguatan Nilai-Nilai Moderasi Beragama Melalui Kegiatan Keagamaan Masyarakat di Desa Cukir, Diwek Jombang - Saefrudin; M. Hanif Satria Budi (LP3M IAIFA Kediri, 2025)
Abstract Strengthening the values of religious moderation is paramount in efforts to overcome diversity. The word lan moderation in religion is al-wasathiyah. In fact, in the field, religious moderation carried out in Cukir Jombang Village is carried out in a family manner in Islamic religious activities which include Islamic organisations, celebrations of Islamic holidays, and routine recitation. The implementation of this research is aimed at evaluating the model of implementing religious moderation in Cukir Jombang Village, by implementing three data collection models, namely documentation, observation, and interviews. The research location is Cukir Village, Diwek District, Jombang Regency. Based on the results of observations, it was found that religious activities at the Al-Qur'an Education Park acted as a place to spread love for humanity, introduce the value of moderation, and national ideas. Religious activities in Cukir Village, Diwek District, Jombang Regency run optimally and have a positive impact and are involved in strengthening Islamic religious organisations in various activities, fostering, and creating peace between religions and Muslims. Keywords: Strengthening, Moderation Values, Religious Activities